2022
DOI: 10.3389/fbioe.2022.837639
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative Endodontics and Minimally Invasive Dentistry: Intertwining Paths Crossing Over Into Clinical Translation

Abstract: Regenerative endodontic procedures have been described for over a decade as a paradigm shift in the treatment of immature necrotic permanent teeth, owing to their ability to allow root maturation with subsequent enhancement of the tooth’s fracture resistance in addition to the potential for regeneration of vital intracanal tissues. Concomitantly, minimally invasive endodontics is another rising concept with the main concern of preservation of tooth structure. Stemming from their potential to preserve the origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 71 publications
(97 reference statements)
0
19
0
1
Order By: Relevance
“…These insults to the dentin–pulp complex can increase patient pain and, if left untreated, tooth loss and serious damage to surrounding tissues. Currently, there are only two strategies available to treat deep cavitated lesions . First, vital pulp therapy harnesses the healthy stem cell population within the dental pulp to induce odontoblast-like cells to differentiate, replace the damaged population, and form a dentinal bridge with scar tissue.…”
Section: Cap Delivery Systems For Dentin Regeneration and Biominerali...mentioning
confidence: 99%
See 1 more Smart Citation
“…These insults to the dentin–pulp complex can increase patient pain and, if left untreated, tooth loss and serious damage to surrounding tissues. Currently, there are only two strategies available to treat deep cavitated lesions . First, vital pulp therapy harnesses the healthy stem cell population within the dental pulp to induce odontoblast-like cells to differentiate, replace the damaged population, and form a dentinal bridge with scar tissue.…”
Section: Cap Delivery Systems For Dentin Regeneration and Biominerali...mentioning
confidence: 99%
“…Currently, there are only two strategies available to treat deep cavitated lesions. 97 First, vital pulp therapy harnesses the healthy stem cell population within the dental pulp to induce odontoblast-like cells to differentiate, replace the damaged population, and form a dentinal bridge with scar tissue. Second, if the dentin–pulp damage is irreversible, then a root canal is performed that causes the loss of the vasculature, innervation, and stem cell population which drastically reduces the longevity of the tooth.…”
Section: Cap Delivery Systems For Dentin Regeneration and Biominerali...mentioning
confidence: 99%
“…The occlusal and cervical portions of the tooth are less stressed according to the Consortium for Educational Communication (CEC) design, which preserves more of the coronal tooth structure (Yuan et al, 2016). As a result, the tooth's ability to withstand masticatory stresses may be enhanced by a minimal canal preparation with a reduced taper [ 20 ].…”
Section: Reviewmentioning
confidence: 99%
“…At this point, it is necessary to clean off any remaining dirt and smear layer. There is a strong correlation between root canal infection and treatment failure, as shown by the large majority of patients who do not respond well to regenerative endodontic [ 20 ]. Research by Plotino and colleagues found that an instrument with a 25-size bore provided a better canal surface in the root canal's apical third [ 35 ].…”
Section: Reviewmentioning
confidence: 99%
“…Regenerative medicine has multiple potential applications and is geared towards the healing or substitution of damaged tissues to restore the previous function. The application of regenerative medicine in dentistry is motivated by the need of more personalized therapies and minimally invasive treatments [ 1 , 2 , 3 ]. Morbidity reduction and enhancing tissue healing (time and quality) would allow the clinicians to offer a better treatment to their patients.…”
Section: Introductionmentioning
confidence: 99%